Advances in human cardiac 31P-MR spectroscopy: SLOOP and clinical applications. - von Kienlin, M; Beer, M; Greiser, A; Hahn, D; Harre, K; Köstler, H; Landschütz, W; Pabst, T; Sandstede, J; Neubauer, S (2001)
Phosphorus magnetic resonance spectroscopy (31P-MRS) has revealed a lot about the biochemistry of physiological and pathological processes in the heart. Nevertheless, until today, cardiac 31P-MRS has not had any clinical impact, albeit some pioneering studies demonstrated that 31P-MRS can indeed provide diagnostic information. In this paper, the development of techniques for human cardiac 31P-MRS over the past decade is reviewed, and the requirements for a reliable clinical measurement protocol are discussed. Spatial localization with optimal pointspread function (SLOOP) is a new method to achieve spatial localization and absolute quantitation. Its properties are detailed, and preliminary findings in patients with dilated cardiomyopathy or myocardial infarction are presented.